It’s homework I been stuck on the problem for 20 mins

The given transformation is:
[tex]g(x)=6f(8x)+1[/tex]What we do is to express the x in f(x) as a product and 8 and another number.
• 80=8 x 10
,• -56=8 x -7
,• -32 = 8 x -4
,• 8=8 x 1
Therefore:
[tex]\begin{gathered} g(10)=6f(8\times10)+1=6f(80)+1=6(-9)+1=-14 \\ \implies x=10,g(x)=-14 \\ \\ g(-7)=6f(8\times-7)+1=6f(-56)+1=6(-2)+1=-11 \\ \implies x=-7,g(x)=-11 \\ \\ g(-4)=6f(8\times-4)+1=6f(-32)+1=6(5)+1=31 \\ \implies x=-4,g(x)=31 \\ \\ g(1)=6f(8\times1)+1=6f(8)+1=6(7)+1=43 \\ \implies x=1,g(x)=43 \end{gathered}[/tex]The completed table is, therefore: